Subsidiarity as Judicial and Legislative Review Principles in the European Union - Moens, Gabriel; Trone, J. (Springer, 2014)
The founding Treaties of the European Union make clear that subsidiarity is a judicially enforceable legal principle. However, the case law of the Court of Justice reveals that the enforcement of subsidiarity as a judicial principle has been ineffective. The Court has applied a very weak standard of review for both substantive and procedural compliance with the subsidiarity principle. By far the most significant application of the subsidiarity principle is its consideration as part of the EU legislative process. A Member State legislature may issue a reasoned opinion regarding subsidiarity aspects of a proposal. These reasoned opinions may trigger the yellow card procedure, forcing the Commission to review its proposal, or the orange card procedure, where the Parliament or Council can block the proposal. These procedures have some potential as legislative safeguards of subsidiarity: in 2013 the Commission withdrew a legislative proposal after the yellow card procedure was activated.